Updates of Adjuvant Therapy in Pancreatic Cancer: Where Are We and Where Are We Going? - Li, Jia; Merl, Man Yee; Chabot, John; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2010)
Pancreatic cancer represents the 4th leading cause of cancer deaths in the United States. Surgical resection remains the only potential curative approach. Current standard adjuvant therapy is gemcitabine monotherapy for 6 months. This year several trials investigated other combinations with or without molecular target agents, with or without concurrent radiation attempting to optimize adjuvant therapy. Several abstracts presented at the 2010 American Society of Clinical Oncology (ASCO) Annual Meeting are highlighted here and will be further discussed in this review article. Abstracts #4012, #4059, and TPS226 added immunotherapy to adjuvant treatment. Abstract #4034 demonstrated lack of efficacy by adding either cetuximab or bevacizumab to known adjuvant therapies. Abstract e14625 combined S-1 to gemcitabine and abstract #4113 demonstrated a positive correlation between symptoms and CA 19-9 levels with the length of survival. Image: Yale-New Haven Hospital. New Haven, CT, USA.